Involvement of extracellular vesicles in the progression, diagnosis, treatment, and prevention of whole-body ionizing radiation-induced immune dysfunction - Seim, Roland F.; Herring, Laura E.; Mordant, Angie L.; Willis, Micah L.; Wallet, Shannon M.; Coleman, Leon G.; Maile, Robert (Frontiers in Immunology, 2023)
Acute radiation syndrome (ARS) develops after exposure to high doses of ionizing radiation and features immune suppression and organ failure. Currently, there are no diagnostics to identify the occurrence or severity of exposure and there are limited treatments and preventative strategies to mitigate ARS. Extracellular vesicles (EVs) are mediators of intercellular communication that contribute to immune dysfunction across many diseases. We investigated if EV cargo can identify whole body irradiation (WBIR) exposure and if EVs promote ARS immune dysfunction. We hypothesized that beneficial EVs derived from mesenchymal stem cells (MSC-EVs) would blunt ARS immune dysfunction and might serve as prophylactic radioprotectants. Mice received WBIR (2 or 9 Gy) with assessment of EVs at 3 and 7 days after exposure. LC-MS/MS proteomic analysis of WBIR-EVs found dose-related changes as well as candidate proteins that were increased with both doses and timepoints (34 total) such as Thromboxane-A Synthase and lymphocyte cytosolic protein 2. Suprabasin and Sarcalumenin were increased only after 9 Gy suggesting these proteins may indicate high dose/lethal exposure. Analysis of EV miRNAs identified miR-376 and miR-136, which were increased up to 200- and 60-fold respectively by both doses of WBIR and select miRNAs such as miR-1839 and miR-664 were increased only with 9 Gy. WBIR-EVs (9 Gy) were biologically active and blunted immune responses to LPS in RAW264.7 macrophages, inhibiting canonical signaling pathways associated with wound healing and phagosome formation. When given 3 days after exposure, MSC-EVs slightly modified immune gene expression changes in the spleens of mice in response to WBIR and in a combined radiation plus burn injury exposure (RCI). MSC-EVs normalized the expression of certain key immune genes such as NFκBia and Cxcr4 (WBIR), Map4k1, Ccr9 and Cxcl12 (RCI) and lowered plasma TNFα cytokine levels after RCI. When given prophylactically (24 and 3 hours before exposure), MSC-EVs prolonged survival to the 9 Gy lethal exposure. Thus, EVs are important participants in ARS. EV cargo might be used to diagnose WBIR exposure, and MSC-EVs might serve as radioprotectants to blunt the impact of toxic radiation exposure.